Pengaruh Lingkungan Kerja Kompensasi Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan - Saloka, Yoga Haryo; , Drs. Wiyadi, M.M, Ph.D (2017)
This study uses a quantitative approach that examines the effect of the work environment, compensation, leadership, and motivation on employee performance. In this study took a sample of PD. BPR Giri Sukadana Wonogiri. The sample used in this study were 30 respondents. This analysis tool as a hole is a statistical description, test requirements analysis, classic assumption test and multiple linear regression.. The findings indicate that partially or simultaneously work environment, leadership, compensation, and otivationpositive and significant impact on employee performance. R Square 0,777 indicates that the variation of work environment, leadership, compensation, and motivation are able to explain the performance of employees is 77.7% and the remaining 22.23% is influenced by other variables.